Meta Analysis of the Effectiveness of the STEM Approach to 21st Century Skills in High School Physics Learning - Anggreiny, Lavenia Puspa; Limbong, Ezra Egidia Shelomitha; Simanjuntak, Andrew (PT FORMOSA CENDEKIA GLOBAL, 2023)
One of the impacts of rapid globalization is the need for education in Indonesia. The current educational challenge is that education must be able to produce human resources (HR) who are equipped with all the skills of the 21st century. The STEM approach to learning is a recommendation for improving 21st century abilities. The STEM approach is a learning approach that emphasizes the relationship between science knowledge and skills, technology, engineering, and mathematics to overcome problems. The aim of this research is to determine the effectiveness of using the STEM approach for 21st century abilities. In this research, the Meta Analysis method is used with data analysis techniques for calculating effect sizes. The sample used in this research was 24 online article items that already had an ISSN. The results of the research that has been carried out can conclude that the STEM approach is efficiently used for 21st century abilities with the results of research data, namely; 1). The average effect size of the STEM approach on 21st century abilities is 1.6 on creative thinking, 2.78 on critical thinking, 4.94 on communication and 3.96 on collaboration; 2). The learning model that is most suitable for using a STEM approach to 21st century abilities is the blended learning model of 3.435 with the most appropriate material, namely business and energy material which has an average effect size of 6.24. 3). Based on the class level that effectively uses the STEM approach, namely high school class X with the very high category, it gets an effect size of 4.05.